Health Expenditures, Services and Outcomes in Africa - Peters, David H.; Kandola, Kami; Elemendorf, A. Edward; Chellaraj, Gnanaraj (World Bank, Washington, DC, 2012)
In the past thirty years, Sub-Saharan African countries have made remarkable improvements in health conditions and status. However, they still suffer from some of the worst health problems in the world, and AIDS is making conditions much worse than they will be otherwise. This study, health expenditures, services, and outcomes in Africa considers 48 countries of Sub-Saharan Africa and outlines broad patterns of health spending, service delivery, mortality, fertility and nutrition in the early to mid-1990s. The study focuses on how to better monitor progress and use information to identify problems and improve health outcomes within and among different African countries. Good information about inputs, processes and results in the health sector is vital for policymakers to make intelligent choices about health strategies and investments, and often is simply not available. For purposes of the study, countries were classified as lowest-income, low-income and middle-income categories. Over three quarters of the African countries are low income or even lowest income countries, and nearly all have weak health management systems.